Application of bio-based materials to crack and patch repair methods in concrete. (18th July 2022) - Kawaai, K.; Nishida, T.; Saito, A.; Hayashi, T.
Highlights: The effectiveness of bio-based repair materials was presented and highlighted. The resistance against ingress of water was enhanced by alginate-based healing agents. Re-deterioration in patch repair method was prevented by the use of Bacillus subtilis (natto). The use of Bacillus subtilis (natto) was proved to work as a cathodic inhibitor. Abstract: This study explored the application of bio-based repair materials to concrete for crack repair and patch repair methods. First, the concept of crack repair using Bacillus subtilis (natto) under wet conditions is presented. In addition to the self-healing efficiency, enhancement of corrosion resistance owing to consumption of dissolved oxygen by bacteria which could work as a cathodic inhibitor is theoretically explained by electro-chemical reactions. And then, this study exemplified the application of the bio-based repair material to concrete with respect to crack repair and patch repair methods. First, alginate-based self-healing materials (in-situ encapsulation) are newly developed in this study to improve the resistance against ingress of water in cracked mortar specimens, which is demonstrated by the reduced absorption of water. This is adequately explained by the fact that the calcite precipitation in gel films formed in crack is highly effective in sealing crack in mortar specimen. In addition, the healing agents could reduce the concentration of dissolved oxygen in concrete, which is found to contribute to reduction of the macrocell corrosion current density in which the corrosion rate is determined by the cathodic reactions associated with diffusion of dissolved oxygen. The use of Bacillus subtilis (natto) is highly advantageous in preventing re-deterioration owing to macrocell corrosion taking place between patch repair region and surrounding concrete containing chloride.